2008
DOI: 10.1097/01.njh.0000319177.25294.e5
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Hospices' Use of Complementary Therapy

Abstract: As people live longer with chronic illnesses, the need for hospice services will increase. Complementary therapies have been shown to increase ease, relieve pain, and improve quality of life; all relevant for people with chronic illness at the end of their lives. The first aim of this study was to identify complementary therapy services available to, and provided for, clients receiving hospice care in Nevada and Montana. The second aim was to identify differences in those therapies for urban and rural hospice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 32 publications
(24 reference statements)
1
39
0
Order By: Relevance
“…3 Hospices who offer music therapy as a discretionary service report that it is a patient-preferred therapy compared to other complementary modalities. 4 Patients expect multiple benefits from music therapy, including emotional and spiritual support, support coping with pain, and an opportunity to express feelings. 5 Emotional distress, pain management, and attention to spiritual needs are critical to high quality end of life care.…”
Section: Introductionmentioning
confidence: 99%
“…3 Hospices who offer music therapy as a discretionary service report that it is a patient-preferred therapy compared to other complementary modalities. 4 Patients expect multiple benefits from music therapy, including emotional and spiritual support, support coping with pain, and an opportunity to express feelings. 5 Emotional distress, pain management, and attention to spiritual needs are critical to high quality end of life care.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In studies conducted in other countries with the elderly, it has been shown that rates of complementary and alternative medicine use ere between 28% and 50%. [17,18] Massage is one of the commonly utilized techniques as complementary or alternative methods. According to a research in England, 70% of complementary therapies used in palliative care includes massage.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, people receiving palliative and EoL often use CAM to relieve pain, maintain comfort and quality of life and manage the spiritual aspects of dying to achieve a 'good death' [41,42]. CAM is also used to reduce restlessness, agitation and mental stress [43].…”
Section: Complementary and Alternative Therapiesmentioning
confidence: 99%